Renal control of life-threatening malarial anemia - Qian Wu; Euclides Sacomboio; Lara Valente de Souza; Rui Martins; Jamil Kitoko; Sílvia Cardoso; Temitope W. Ademolue; Tiago Paixão; Jaakko Lehtimäki; Ana Figueiredo; Caren Norden; Pierre-Louis Tharaux; et al. (Cell Reports, 2023)
Summary: Iron recycling prevents the development of anemia under homeostatic conditions. Whether iron recycling was co-opted as a defense strategy to prevent the development of anemia in response to infection is unclear. We find that in severe Plasmodium falciparum malaria, the onset of life-threatening anemia is associated with acute kidney injury (AKI), irrespective of parasite load. Using a well-established experimental rodent model of malaria anemia, we identify a transcriptional response that endows renal proximal tubule epithelial cells (RPTECs) with the capacity to store and recycle iron during P. chabaudi chabaudi (Pcc) infection. This response encompasses the induction of ferroportin 1/SLC40A1, which exports iron from RPTECs and counteracts AKI while supporting compensatory erythropoiesis and preventing the onset of life-threatening malarial anemia. Iron recycling by myeloid cells is dispensable to this protective response, suggesting that RPTECs provide an iron-recycling salvage pathway that prevents the pathogenesis of life-threatening malarial anemia.